2010
DOI: 10.3354/dao02148
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression analyses of hepatocellular adenoma and hepatocellular carcinoma from the marine flatfish Limanda limanda

Abstract: At selected sites around the UK, the offshore sentinel flatfish species dab Limanda limanda are found to contain elevated levels of macroscopic liver tumors. Previous proteomic and metabolomic studies have demonstrated that differences exist between tumor and non-tumor tissues; however, these differing features were not identified, and little is known about the changes at the gene expression level, or whether prognostic markers are present and can be identified. A flounder Platichthys flesus custom cDNA microa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 55 publications
2
16
1
Order By: Relevance
“…In, for example, the Brunsbuttel samples compared with non-tumour bearing Alde fish, choline, phosphocholine and glycine increased, and lactate decreased. Additionally, transcripts for ribosomal proteins showed co-ordinated induction in bulk tumours from dab, indicative of proliferation [22], but no such induction was apparent from the present samples. The changes in gene expression and metabolites detected in this study do not recapitulate those found in bulk tumours, and may be viewed as indicating either an earlier stage of tumourigenesis or a permissive micro-environment in which hyperplastic tissue may form and lead to tumour formation.…”
Section: Discussioncontrasting
confidence: 69%
“…In, for example, the Brunsbuttel samples compared with non-tumour bearing Alde fish, choline, phosphocholine and glycine increased, and lactate decreased. Additionally, transcripts for ribosomal proteins showed co-ordinated induction in bulk tumours from dab, indicative of proliferation [22], but no such induction was apparent from the present samples. The changes in gene expression and metabolites detected in this study do not recapitulate those found in bulk tumours, and may be viewed as indicating either an earlier stage of tumourigenesis or a permissive micro-environment in which hyperplastic tissue may form and lead to tumour formation.…”
Section: Discussioncontrasting
confidence: 69%
“…In light of data presented in the present study, it will now be important to consider the relationship between elevated liver cancer prevalence and potential causal factors at offshore sites. Studies demonstrating potential offshore endocrine disruption effects in populations of dab from the Dogger Bank region of the North Sea (Stentiford & Feist 2005, Scott et al 2007) and the recent finding of over-expression of vitellogenin mRNA in liver tumours of dab (Small et al 2010) are provocative directors for further research investigating the relationship between liver-cancer formation and the endocrine system of marine fish and their elevated association with particular geographic locations (Stentiford et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…UK sites exceeding 20%. [31][32][33][34][35] However, the causative factors of these tumors and the molecular mechanisms involved, especially the balance between epigenetic and genetic factors, is unclear. Previous studies in our laboratory indicated that mutation profiles of oncogenes and tumor-suppressor genes within tumors were different between fish species and humans.…”
Section: Introductionmentioning
confidence: 99%